2022
DOI: 10.1109/tgrs.2022.3201146
|View full text |Cite
|
Sign up to set email alerts
|

Flash Floods Prediction Using Precipitable Water Vapor Derived From GPS Tropospheric Path Delays Over the Eastern Mediterranean

Abstract: A flash flood is a rapid and intense response of a drainage area to heavy rainfall events. In the arid and semi arid parts of the Eastern Mediterranean (EM) region, the spatiotemporal distribution of rainfall is the most important factor for flash flood generation. A possible precursor to heavy rainfall events is the rise in tropospheric water vapor amount, which can be remotely sensed using ground based Global Navigation Satellite Systems (GNSS) stations. Here, we use the Precipitable Water Vapor (PWV) derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 62 publications
(53 reference statements)
0
23
0
Order By: Relevance
“…The study on agricultural drought indices can be performed based on the proposed model for improving the accuracy and spatial-temporal resolutions of drought monitoring. Furthermore, more datasets of GNSS-PWV and meteorological data are required to develop near real-time applications for flood and drought monitoring [ 53 , 84 ]. Therefore, the developed model is a potential alternative approach to estimate the daily PET and beneficial to climate and agricultural research works for alleviating the adverse impacts by global warming and extreme weather events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study on agricultural drought indices can be performed based on the proposed model for improving the accuracy and spatial-temporal resolutions of drought monitoring. Furthermore, more datasets of GNSS-PWV and meteorological data are required to develop near real-time applications for flood and drought monitoring [ 53 , 84 ]. Therefore, the developed model is a potential alternative approach to estimate the daily PET and beneficial to climate and agricultural research works for alleviating the adverse impacts by global warming and extreme weather events.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is an alternative technology that is efficiently utilized to obtain water vapor with continuous data and high temporal resolutions in all-weather. Furthermore, it has been applied in various research works such as hydrological application [ 48 ], forecasting precipitation [ [49] , [50] , [51] ], monitoring and estimating snow evaporation [ 52 ], predicting flash floods [ 53 ], assessing the PET [ 54 , 55 ] and evaluating the drought index [ 56 ]. In Thailand, the previous studies found the study of spatial and temporal variability and the validation of PWV value from GNSS observations [ [57] , [58] , [59] ].…”
Section: Introductionmentioning
confidence: 99%
“…Water vapor is paramount in climate change [1], the hydrological cycle, heat exchange and transfer due to spatiotemporal variability, the natural greenhouse effect and latent heat released by condensation [2]. Therefore, an accurate representation of water vapor concentration is crucial for numerical weather prediction [3], extreme weather monitoring [4] and global and regional scale climate models.…”
Section: Introductionmentioning
confidence: 99%
“…PWV is strongly associated with precipitation, extreme weather events (typhoons, hurricanes, etc. ), and climate [11][12][13][14][15]. High-accuracy ZWD enhances GNSS application performance in extreme weather monitoring and early warning.…”
Section: Introductionmentioning
confidence: 99%